Peningkatan Kualitas Proses Perkuliahan Laser dan Serat Optik dengan Menggunakan Program ELIZA pada Mahasiswa 2007 di Jurusan Fisika Unesa - Aditya Prapanca, ; Nadi Suprapto, ; Asnawi, (Widya Cendika, 2011)
Laser and Fiber Optics course is one of the subject option that is very important. It must be mastered by the students taking the instrumentation and computing skills program. The results of previous observations, namely the Laser and Fiber Optics Subject year 2008/2009 toward the physic students, shows the results of the subject is still less satisfactory. It is caused by the students who do not understand the materials. It can be seen from the lack of active participation in class numbers. As a result the students do not have motivation to ask and answer the questions. By using action research, there is an imprivement toward the students participation in Lasers and Fiber Optics subject. The first cycle shows that there are 22 students who are active in this subject. And in the second cycles, there are 36 students who are active. It means there is an improvement.